Languages and materialities in contemporary art: the place of early childhood education and children in this debate (Olhar de Professor, 2021)
The purpose of this text is to discuss the different types of relationships between contemporary art, languages and materialities with children. For that, we mobilize concepts and experiences from which we discuss the multiple languages and materialities that are intrinsic in the children's experiences and that dialogue with the contemporary art way of being. For this debate we will discuss how the terms “different languages” and ‘Multiple languages” are present in official curricular documents in the city of São Paulo and Brazil. We will also discuss the specificity and possibilities that contemporary art offers for early childhood education.Keywords: Early childhood education; contemporary art; materialities.
Keywords: Early childhood education. Contemporary art. Materialities.